Detrimental Role for Human High Temperature Requirement Serine Protease A1 (HTRA1) in the Pathogenesis of Intervertebral Disc (IVD) Degeneration - Tiaden, André N. (American Society for Biochemistry and Molecular Biology, 2012)
Human HTRA1 is a highly conserved secreted serine protease that degrades numerous extracellular matrix proteins. We have previously identified HTRA1 as being up-regulated in osteoarthritic patients and as having the potential to regulate matrix metalloproteinase (MMP) expression in synovial fibroblasts through the generation of fibronectin fragments. In the present report, we have extended these studies and investigated the role of HTRA1 in the pathogenesis of intervertebral disc (IVD) degeneration. HTRA1 mRNA expression was significantly elevated in degenerated disc tissue and was associated with increased protein levels. However, these increases did not correlate with the appearance of rs11200638 single nucleotide polymorphism in the promoter region of the HTRA1 gene, as has previously been suggested. Recombinant HTRA1 induced MMP production in IVD cell cultures through a mechanism critically dependent on MEK but independent of IL-1β signaling. The use of a catalytically inactive mutant confirmed these effects to be primarily due to HTRA1 serine protease activity. HTRA1-induced fibronectin proteolysis resulted in the generation of various sized fragments, which when added to IVD cells in culture, caused a significant increase in MMP expression. Furthermore, one of these fragments was identified as being the amino-terminal fibrin- and heparin-binding domain and was also found to be increased within HTRA1-treated IVD cell cultures as well as in disc tissue from patients with IVD degeneration. Our results therefore support a scenario in which HTRA1 promotes IVD degeneration through the proteolytic cleavage of fibronectin and subsequent activation of resident disc cells.